THE DEVELOPMENT OF STUDENT WORKSHEET BY USING GUIDED INQUIRY LEARNING MODEL TO TRAIN STUDENT'S SCIENTIFIC ATTITUDE - Misbah, Misbah; Dewantara, Dewi; Hasan, Sayid Muhammad; Annur, Syubhan (Unnes Science Education Journal, 2018)
This research is aimed to develop student’s worksheet using guided inquiry learning model to train senior high school students’ scientific attitude on the dynamic electricity subject. The specific purposes of this research are to (1) describe the validity of student worksheet, (2) describe the practicality of student worksheet based on questionnaire responses, (3) describe the effectiveness of student worksheet based on students’ cognitive result, and (4) describe the achievement of students’ scientific attitude ability. This research uses research and development methods with ADDIE design. The research shows that: (1) the student worksheet validity is categorized as very valid, (2) the practicality of the student worksheet based on questionnaire responses is categorized as practical, (3) the effectiveness of student worksheet is categorized as effective, and (4) the achievement of students’ scientific attitude ability is moderate. In conclusion, student worksheet using guided inquiry learning model to train students’ scientific attitude for senior high school on the dynamic electricity subject is eligible to be used in the learning process.